Demand Management: A Critical Component in Supply Chain - Pitnerová, Ing. Kate?ina (ExcelingTech, 2024)
Effective planning is one of the tools that affect not only the profitability of the services/goods offered, but also the very existence of the company. In recent years, there has been a steady increase in the number of books published on the subject. It is also possible to observe the use of advanced techniques for forecasting demand. This paper analyses in detail demand shaping strategies and their impact on supply chain efficiency and presents possible tools for its management. The analysis concludes that the best tolls of demand management rely on specific needs and circumstances of a business.